2014
DOI: 10.1371/journal.pone.0087383
|View full text |Cite
|
Sign up to set email alerts
|

Novel Marker for the Onset of Frontotemporal Dementia: Early Increase in Activity-Dependent Neuroprotective Protein (ADNP) in the Face of Tau Mutation

Abstract: Tauopathy, a major pathology in Alzheimer's disease, is also found in ∼50% of frontotemporal dementias (FTDs). Tau transcript, a product of a single gene, undergoes alternative splicing to yield 6 protein species, each with either 3 or 4 microtubule binding repeat domains (tau 3R or 4R, associated with dynamic and stable microtubules, respectively). While the healthy human brain shows a 1/1 ratio of tau 3R/4R, this ratio may be dramatically changed in the FTD brain. We have previously discovered that activity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 55 publications
2
40
0
1
Order By: Relevance
“…Using biochemical and cell biology techniques, we showed multiple crucial interactions for ADNP, including the chromatin remodeling complex SWI/SNF , the RNA splicing machinery (Schirer et al 2014), protein translation (Malishkevich et al 2015), as well as the microtubule (Oz et al 2014) and autophagy systems (Merenlender-Wagner et al 2015). However, no good science can exist without listening and watching the society needs and hearing out the parents and wonderful caretakers of the ADNP children, which follows herein (Sandra Bedrosian Sermone, Our Undiagnosed Genetic Journey-ADNP mutation, 2015).…”
mentioning
confidence: 99%
“…Using biochemical and cell biology techniques, we showed multiple crucial interactions for ADNP, including the chromatin remodeling complex SWI/SNF , the RNA splicing machinery (Schirer et al 2014), protein translation (Malishkevich et al 2015), as well as the microtubule (Oz et al 2014) and autophagy systems (Merenlender-Wagner et al 2015). However, no good science can exist without listening and watching the society needs and hearing out the parents and wonderful caretakers of the ADNP children, which follows herein (Sandra Bedrosian Sermone, Our Undiagnosed Genetic Journey-ADNP mutation, 2015).…”
mentioning
confidence: 99%
“…ADNP is a member of the SWI/SNF chromatin remodeling complex , which is associated with transcription and splicing (Batsche et al 2006). ADNP expression was previously shown to be correlated with tau 3R expression (Schirer et al 2014). We also showed a direct interaction of ADNP with protein associated splicing factor (PSF) (Schirer et al 2014), which was found to associate with the SWI/SNF-like complex (Ito et al 2008) and also with tau splicing.…”
Section: Activity-dependent Neuroprotective Protein Nap and Tausupporting
confidence: 53%
“…ADNP expression was previously shown to be correlated with tau 3R expression (Schirer et al 2014). We also showed a direct interaction of ADNP with protein associated splicing factor (PSF) (Schirer et al 2014), which was found to associate with the SWI/SNF-like complex (Ito et al 2008) and also with tau splicing. PSF suppresses tau exon 10 inclusion by interacting with a stem-loop structure downstream of exon 10 (Ray et al 2011).…”
Section: Activity-dependent Neuroprotective Protein Nap and Tausupporting
confidence: 53%
“…Alternatively the calcium dysregulation or kinase activation in response to ketamine might also alter tau splice forms. An alteration in tau isoforms with an increase in the tau isoform with four microtubule binding domains increased expression of ADNP (Schirer et al, 2014). Thus ketamine might alter the tau isoform ratios, which then signal of neurodegeneration and/or stress to the neuron.…”
Section: Discussionmentioning
confidence: 99%
“…Even mice with only half the concentration of ADNP demonstrate increased neurodegeneration with increased age (Vulih-Shultzman et al, 2007). ADNP's mechanism of action may be a regulator of gene transcription during early development (Pinhasov et al, 2003) or a regulator of splicing and transcription through its potential binding with heterochromatin protein (HP) 1a and Brahma (Brm), a component of the SWItch/Sucrose NonFermentable (SWI/SNF) chromatin remodeling complex (Schirer et al, 2014). Additional evidence for ADNP's function correlated a human mutation in exon 5 of ADNP with autism and increased expression of ADNP-1 and ADNP-2 mRNA (Helsmoortel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%